2007
DOI: 10.1007/bf03262570
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of the effectiveness of a one-step conditioning agent in fissure sealant placement: 12 month results

Abstract: The best practice for placement of sealants remains enamel preparation with acid etch and use of an intermediate bonding layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 16 publications
1
32
1
2
Order By: Relevance
“…They concluded that the best practice for placement of sealants remains enamel preparation with acid etch and use of an intermediate bonding layer. 17 Contrary to the findings of the current study, Feigal and Quelhas 12 reported similar sealant retention rates using Prompt-L-Pop adhesive and conventional phosphoric acid etching without the use of any bonding agent in vivo. However, the results cannot be directly compared with our results, as no adhesive system was used in conjunction with the phosphoric acid.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…They concluded that the best practice for placement of sealants remains enamel preparation with acid etch and use of an intermediate bonding layer. 17 Contrary to the findings of the current study, Feigal and Quelhas 12 reported similar sealant retention rates using Prompt-L-Pop adhesive and conventional phosphoric acid etching without the use of any bonding agent in vivo. However, the results cannot be directly compared with our results, as no adhesive system was used in conjunction with the phosphoric acid.…”
Section: Discussioncontrasting
confidence: 55%
“…In another clinical study, the effects of a self-etch adhesive system and a conventional acid etching on retention of a fissure sealant were compared. 17 It has been found that at the end of a 12-month period, the retention of the acid-etch group was significantly superior to that of the self-etch group. They concluded that the best practice for placement of sealants remains enamel preparation with acid etch and use of an intermediate bonding layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies were excluded because reported data of the same sample in different papers. In these cases, studies that reported data from the longer follow‐up were considered. One article was a retrospective study of chart review, one did not use acid‐etching approach as control group, and another study used acid etching before self‐etch system, without a proper group of comparison (only self‐etch adhesive system).…”
Section: Resultsmentioning
confidence: 99%
“…This approach can be an alternative to increase the adhesion [33] and decrease microleakage in case of cavitaded occlusal lesions [34-38], as well as decline clinically the risk of failures of the sealants, especially in occlusal surfaces [35] and enhance the retention and longevity of this material [39]. In our study we used a conventional adhesive system prior sealant application in order to achieve better retention of the material in caries lesions that reached dentin, a more humid substrate that could negatively influence the retention results.…”
Section: Discussionmentioning
confidence: 99%